Integration of biofeedback into physical therapy - Buriachenko, Vadym; Buriachenko, Nadiia; Astapova, Yana (My University, 2025)
Biofeedback is a modern physical therapy method that allows patients to consciously control their body's physiological processes. Biofeedback therapy is effective in treating various conditions, including chronic pain, anxiety disorders, hypertension, and migraines. It is also used in rehabilitation after injuries, helping to restore muscle function and improve motor skills.
Keywords: biofeedback therapy; physical therapy; 2025а